Rooms of their own: old rituals in new settings: women between Sufism and Islamic activism in contemporary Istanbul - Catharina Raudvere (Scripta Instituti Donneriani Aboensis, 1999)
This paper deals with how rituals, deeply rooted in local tradition, can be used to legitimize new forms of activism in complex modern societies. The empirical material comes from fieldwork in Istanbul, where the author has studied a small Muslim women's group. The women have organized their activities in the form of a religious foundation, offering regular prayer meetings and basic religious education to other women in the vicinity. The women's use of the term vakif  comprises both the formal organisation and the meeting place as such. The weekly performance of the repetitive and intense zikir-prayer constitutes the core of activities and the teachings of the leading women and their theology is clearly based on sufi, tasavvuf, thought. They identify themselves as the keepers of sufi traditions, but without any formal connection to any established order, tarikat. Many of the formal aspects of their religious life follow established patterns, but the social and cultural setting in the mega-city of Istanbul is a novelty. From the conditions of modern urban life follows a wider complexity in individual intention and interpretation of the rituals.